2013
DOI: 10.1111/asj.12034
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of ferritin and anti‐ferritin autoantibodies in serum and colostrum of Holstein and Japanese Black cows

Abstract: Anti-ferritin autoantibody is a ferritin-binding protein commonly found in mammals; it is thought to form an immune complex with ferritin and thereby mediate the rapid clearance of circulating ferritin. The aim of this study is to determine concentrations of ferritin and anti-ferritin autoantibodies (immunoglobulin (Ig)M, IgG and IgA) in serum and colostrum of Holstein (H) and Japanese Black (JB) cows within 24 h of normal calving. Blood and colostrum samples were collected from cows of various ages (2-11 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Ferritin is present in blood and extracellular fluids, including milk. In cows it was found that ferritin concentrations were higher in colostrum than in serum [75], in agreement with [57] who reported a higher ferritin genes expression in human colostrum with respect to mature milk. The expression of M-SAA3.2 gene in the bovine mammary gland was reported by [76] who confirmed the role of this gene in host defense, likely in the neonate gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 80%
“…Ferritin is present in blood and extracellular fluids, including milk. In cows it was found that ferritin concentrations were higher in colostrum than in serum [75], in agreement with [57] who reported a higher ferritin genes expression in human colostrum with respect to mature milk. The expression of M-SAA3.2 gene in the bovine mammary gland was reported by [76] who confirmed the role of this gene in host defense, likely in the neonate gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 80%
“…Although Kanno et al . () developed direct semi‐quantitative measurement of autoantibodies (IgG, IgM and IgA) to ferritin in the sera and colostrum of bovines with ferritin‐coated plates, in this study, the measurement of immunoglobulin classes with ferritin‐binding activity with co‐immunoprecipitation method has been developed. Ferritin is hypothesized to naturally occur as a heteropolymer, suggesting that H‐ or L‐subunit homopolymers are not naturally found.…”
Section: Discussionmentioning
confidence: 97%
“…In bovines, colostral ferritin and maternal autoantibodies (IgG and IgM) to ferritin are likely to be transferred to newborn calves (Kanno et al . ). Colostrum‐fed foals showed a sharp increase in ferritin antibody activities after 2 weeks of age, suggesting that maternal anti‐ferritin autoantibody is passively transferred via colostrum (Wilson et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations